Pandangan fuqaha Maliki terhadap jualbeli sukuk pada zaman Marwan al-Hakam: satu analisis ringkas / Mohd Asyadi Redzuan … [et al.] - Redzuan, Mohd Asyadi (2015)
This paper aims at exploring the characteristics of sukuk during the reign of Marwan bin al- Hakam as well as elucidating the opinions of Malikis on the issue of tradability of that sukuk based on Malikis’ classical literatures. By using library research methodology, this study has found that sukuk was given during the period of Marwan bin al-Hakam on the basis of responsibility of government to provide financial rights or assistance to the government servant as well as to the needy. Majority of the Malikis disapproved the second sale of sukuk (ta’am al-jar) on the ground that this sale is considered as ‘sale of food’ without taking its possession which is prohibited by the Prophet Muhammad p.b.u.h. The logical premise that can be drawn upon this study is that sukuk may not be sufficient to constitute an independent property. Thus, the tradability of sukuk is subject to the types of its underlying asset.